\( 1 \leftarrow \quad \) For \( f(x)=1-x \) and \( g(x)=2 x^{2}+x+2 \), find the following functions. a. \( (f \circ g)(x) ; \) b. \( (g \circ f)(x) \); c. \( (f \circ g)(3) \); d. \( (g \circ f)(3) \) a. \( (f \circ g)(x)=-2 x^{2}-x-1 \) (Simplify your answer.) b. \( (g \circ f)(x)=\square \) (Simplify your answer.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To find \( (g \circ f)(x) \), we need to substitute \( f(x) \) into \( g(x) \). So, we start with: \[ g(f(x)) = g(1 - x) \] Now, substitute \( f(x) = 1 - x \) into \( g(x) = 2x^2 + x + 2 \): \[ g(1 - x) = 2(1 - x)^2 + (1 - x) + 2 \] \[ = 2(1 - 2x + x^2) + (1 - x) + 2 \] \[ = 2 - 4x + 2x^2 + 1 - x + 2 \] \[ = 2x^2 - 5x + 5 \] Thus, b. \( (g \circ f)(x) = 2x^2 - 5x + 5 \). Now, let's evaluate \( (f \circ g)(3) \) and \( (g \circ f)(3) \): For \( (f \circ g)(3) \), we first find \( g(3) \): \[ g(3) = 2(3)^2 + (3) + 2 = 2(9) + 3 + 2 = 18 + 3 + 2 = 23 \] Now, substitute this into \( f \): \[ f(23) = 1 - 23 = -22 \] Therefore, c. \( (f \circ g)(3) = -22 \). Next, let’s find \( (g \circ f)(3) \): We know \( f(3) = 1 - 3 = -2 \). Now we substitute \(-2\) into \( g \): \[ g(-2) = 2(-2)^2 + (-2) + 2 = 2(4) - 2 + 2 = 8 - 2 + 2 = 8 \] Thus, d. \( (g \circ f)(3) = 8 \). In summary: - \( (f \circ g)(x) = -2x^2 - x - 1 \) - \( (g \circ f)(x) = 2x^2 - 5x + 5 \) - \( (f \circ g)(3) = -22 \) - \( (g \circ f)(3) = 8 \)